Synthesis, structural characterization and electrochemical studies of new macrocyclic Schiff base containing pyridine head and its metal complexes - Ilhan, Salih; Temel, Hamdi; Yilmaz, Ismail; Sekerci, Memet (Elsevier Science Sa, 2007)
A new macrocyclic ligand, 1,3,5-triaza-2,4:7,8:13,14-tribenzo-9,12-dioksa-cyclopentadeca-1,5-diene was synthesized by reaction of 2,6-diaminopyridine and 1,2-bis(2-carboxyaldehyde phenoxy)ethane. Then, its Cu(II), Ni(II), Pb(II), Co(III) and La(III) complexes were synthesized by the template effect by the reaction of 2,6-diaminopyridine and 1,2-bis(2-carboxyaldehyde phenoxy)ethane and Cu(NO3)(2)center dot 3H(2)O, Ni(NO3)(2)center dot 6H(2)O, Pb(NO3)(2), Co(NO3)(2)center dot 6H(2)O, La(NO3)(3)center dot 6H(2)O, respectively. The ligand and its metal complexes have been characterized by elemental analysis, IR, H-1 and C-13 NMR, UV-Vis spectra, magnetic susceptibility, thermal gravimetric analysis, conductivity measurements, mass spectra, and cyclic voltammetry. All complexes are diamagnetic and Cu(II) complex is binuclear. The Co(11) was oxidized to Co(111). The comparative electrochemical studies show that the nickel complex exhibited a quasi-reversible one-electron reduction process, while copper and cobalt complexes gave irreversible reduction processes in DMSO solution. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: macrocyclic Schiff base; macrocyclic Schiff base complexes; 2,6-Diaminopyridine and 1,2-bis(2-carboxyaldehyde phenoxy)ethane